Pemanfaatan Ekstrak Etanol Kulit Buah Naga Merah (Hylocereus polyrhizus) Dalam Sediaan Krim Lulur Sebagai Pelembab Alami Kulit - Indra Ginting; Muhammad Andry (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Flavonoid chemicals, vitamins A, C, and E, and polyphenols are found in the skin of red dragon fruit (Hylocereus polyrhizus), which may be utilized as a source of natural antioxidants to fight free radicals and give a moisturizing effect on the skin. Objective: In this study, an ethanol extract of red dragon fruit peel with concentrations of 1%, 3%, and 5% will be used to create a scrub cream preparation. Method: Experiments were used in this study. Organoleptic, homogeneity, dispersion, irritation, stability (cycling), and moisture efficacy tests were among the assessment procedures used to assess the scrub cream formulation. Results: The preparations all have a semisolid consistency, a vanilla scent, and a variety of hues, including white in the blank formula, cream in formulas F1 and F2, brownish cream in recipe F3, and light brown in formula F3. All of the prepared were uniform and did not bother the skin. With a pH range of 5.7–5.9, all preparations satisfied the criteria. With a dispersion of 5.6-7.9, the dispersive power of all preparations fulfilled the standards. There was no discernible change in the stability test during the riding test. The F3 scrub cream preparation had the biggest rise in skin water content from the F0, F1 and F2 preparations, which was 29.4% at week 4 after using the preparation, according to the findings of the moisture efficacy test. Conclusion: The study's findings indicated that red dragon fruit peel extract might be used to create a scrub cream preparation that can moisturize the skin and has passed physical assessment standards.